Coronavirus Diseases (COVID-19): Features, Epidemiology, Mutational variations and Treatments Across India - Sayani Jati; Kanthesh M. Basalingappa; B. Geethanjali; R. Parthiban; S. Prathibha Rajashekara; T.S. Gopenath (Journal of Pure and Applied Microbiology, 2021)
Coronaviruses are a group of enveloped viruses with a longer, undivided single-stranded RNA genome, which cause diseases in a variety of animals and humans. In addition to infecting other economically important animals (such as pigs or chickens), six coronaviruses are known to infect human hosts, causing respiratory illness. Severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle East respiratory syndrome coronavirus (MERS-CoV) are highly pathogenic animal coronaviruses that have produced local, regional, and worldwide outbreaks. It is suspected that the current pandemic, caused by a similar coronavirus (SARS-CoVID-19). A new variant of B.1.617 lineage that causes worry about many countries has been identified first in the UK but it makes the worst scenario in India. This includes mutants with immune prolapse E484K and N501Y mutations. Some new variants recently discovered in India like double & triple mutation due to some specific climatic and environmental conditions. Because it creates a viral exodermis and contacts human cells due to mutations in peplomer proteins. The other type of protein is spike protein, are required to bind to receptors in human cells mutations. It can improve the affinity for human receptors and increase the virus, they can cause immune prolapse and reinfection. Moreover, these viruses are capable of adapting and mutating to the new environment. Our immune system is unable to distinguish them from previous infections due to changes in the structure of proteins. The rapid transmission of the COVID-19 around the world causing a severe mortality rate depends on mutation on their spike protein.